Social support and postpartum adherence to HIV treatment: a community-based participatory research study in Russia. (20th September 2020) - King, Elizabeth J; Yakovleva, Anna; Lisecki, Shelbi R; Shastina, Elena; Sukhova, Natalia; Titina, Elena; Legchilova, Daria; Evdokimova, Irina; Godunova, Julia
Abstract: Background: There are over 1 million people living with HIV in Russia, and less than half of them are on antiretroviral treatment (ART). Earlier in the epidemic, Russia was successful in implementing prevention of mother-to-child transmission programmes; however, there is a gap in knowledge about postpartum adherence to ART among women living with HIV (WLHIV). The objective of our research study was to identify which factors are associated with postpartum engagement in HIV care and treatment in Russia. Methods: We conducted a community-based participatory research study in five Russian cities. We surveyed 200 WLHIV who had given birth within the previous 24 months about their use of ART. We used multivariable logistic regression to determine which types of social support are associated with adherence to ART in the postpartum period. Results: Less than half (40%) of mothers reported being adherent to ART. Multivariable analysis showed that having a supportive family environment [aOR = 2.64, 95% CI (1.91–5.83)], and active engagement with other HIV-positive mothers [aOR = 2.20, 95% CI (1.04–4.66)] were positively associated with postpartum adherence to ART. WLHIV who had more than one child were less likely to be adherent then WLHIV with just one child [aOR = 0.44, 95% CI (0.22–0.91)]. Conclusion: The support that new mothers have or do not have can play an important role in WLHIV adherence to ART. The findings from our study provide ideas for improving the likelihood that women will continue to engage in HIV treatment and care after pregnancy.